Students of Indonesian-Language Politeness through Moral Education at Acehnese Universities - Novi Diana; Istiqamah Istiqamah; Anisaturrahmi Anisaturrahmi (Budapest International Research and Critics University, 2021)
The aim of this study is to examine the conditions of students at Acehnese colleges, institues, and universities and the consequences of Indonesian-language political students who get moral education at the institutions. The method of research is descriptive with a qualitative approach. Islamic educational students from State Islamic University of Ar-Raniry, State Islamic Institute of Langsa, State Islamic Institute of Lhokseumawe, and State College for Islamic Studies of Gajah Putih Takengon serve as the resource persons. Observation, semi-structured interviews, and documentation were used to collect data in this study. Data analysis was accomplished by data reduction, data visualization, and conclusion drawings. The findings of this study shed light on the state of students' politeness at Majority Islamic institution, namely the category of courteous. Additionally, it incorporates admirable principles into its collages. That is, the students who are courteous are pleasant, which is consistent with Luqman's indication of moral education in paragraphs 18-19. The ramifications of this study are significant for student attitudes about language in lectures and in other activities involving the academic community at institutions. Each individual's community life will also be impacted by this civility.